Solitary Fibrous Tumor of the Kidney: A Case Report - Abdullah Demirtaş; Volkan Sabur; Hülya Akgün; Emre Can Akınsal; Deniz Demirci (Case Reports in Urology)
Solitary fibrous tumor is a spindle cell neoplasm mostly originating from pleura; however, it has also recently been reported to be extrapleural. A 57-year-old man presented with left lumbal pain. Ultrasonography and computed tomography showed a cystic lesion of 14 × 11 cm with solid areas and septations in middle and lower poles of the left kidney. Radical nephrectomy was performed. Immunohistochemical studies showed strong reactions with CD34 and CD99. A nuclear positivity with Ki-67 was observed in less than 1% of cells. Despite repeated stainings with vimentin, no clear tumor evaluation could be made due to artifacts. The tumor was negative with Bcl-2, desmin, HMB-45, S100, FVIII, and CD31. Histopathological and molecular studies made the diagnosis of a solitary fibrous tumor. The patient is now currently free of disease at the 26th month of followup.